Health Financing and Household Financial Protection in D.R. Congo: A Vector Autoregressive Model (VaR) Analysis - BINENE SABWE, Emmanuel; LOWENGA KOYAMODJA, Logas; LUBONGO MBILU, Yannick; NTUNGILA NKAMA, Floribert (Theoretical and Practical Research in Economic Fields, 2023)
This paper examines the health-related expenditures of economic agents in the Democratic Republic of Congo (households, government and its external technical and financial partners). Given health care high costs of health care in the DRC, access to appropriate health care is hindered due to low income. As a result, government and its external technical and financial partners indispensably step in to ensure that vulnerable households are protected from ruinous expenses.     At the same time, the paper provides an overview of public finances in the DRC health sector using a theoretical approach and analyzes government intervention effects and their external technical and financial partners intervention effects using a vector autoregressive model (VaR) through random shock simulations and variance decomposition. This analysis is carried out assuming that socioeconomic environment is constant "all things being equal". The result is that household health-related expenditure per capita forecasts can be significantly improved at 0.05 threshold by public health-related expenditure per capita and by health-related expenditure per capita forecasts engaged by external technical and financial partners.